2013
DOI: 10.1371/journal.pone.0082561
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Neuropathological Analysis in Rats with Aluminum Trichloride-Induced Alzheimer's Disease

Abstract: Background and AimsHemodynamic normality is crucial to maintaining the integrity of cerebral vessels and, therefore, preserving the cognitive functions of Alzheimer's disease patients. This study investigates the implications of the hemodynamic changes and the neuropathological diversifications of AlCl3-induced AD.MethodsThe experimental animals were 8- to 12-wk-old male Wistar rats. The rats were randomly divided into 2 groups: a control group and a (+)control group. Food intake, water intake, and weight chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 55 publications
3
14
0
2
Order By: Relevance
“…4). This could be as a result of relatively short period of AlCl 3 treatment in the present study; as findings by Chen et al (2013) in rats fed AlCl 3 for about 6 months showed deposits of amyloid plaques in the hippocampus, perhaps as a result of longer duration of oral exposure to AlCl 3 via the rats' drinking water.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…4). This could be as a result of relatively short period of AlCl 3 treatment in the present study; as findings by Chen et al (2013) in rats fed AlCl 3 for about 6 months showed deposits of amyloid plaques in the hippocampus, perhaps as a result of longer duration of oral exposure to AlCl 3 via the rats' drinking water.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, intracerebroventricular (ICV) injection of STZ in rodents causes Alzheimer's-like pathology, and this model is one of the choice animal models of AD (Khan et al 2012;Du et al 2014;Khan et al 2015). In addition to ICV STZ, aluminium chloride (AlCl 3 ) administered to rodents either orally or intraperitoneally for several weeks can trigger some AD-like pathology (such as senile plaque, etc) (Chen et al 2013) with variable degrees of neurodegeneration. Nevertheless, neither AlCl 3 nor STZ treatment alone has produced sufficient level of brain lesions in rodent models of diseases of neurodegeneration such as AD; moreover, because of the prevalence of diabetes mellitus among AD subjects (Ott et al 1999), novel animal models of AD disease with diabetes mellitus co-morbidity are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Implicações no desempenho da memória e aprendizado podem ser observadas em modelos de DA produzidos por alumínio em ratos. Um estudo analisou as consequências das alterações hemodinâmicas, e a associação entre estas e as modificações neuropatológicas na DA induzida por alumínio (Chen et al, 2013). Dois grupos de 10 ratos foram usados no estudo, sendo categorizados como controle, que não receberam a administração do cloreto de alumínio, e o grupo que recebeu a administração do cloreto de alumínio de um a cinco meses.…”
Section: Alumíniounclassified
“…Al is not a redox active metal, but it is pro-oxidant and can induce the formation of reactive oxygen species (ROS), causing oxidative stress and cell damage in diverse tissues, including the liver and brain [10, 11]. Some lactic acid bacteria (LAB) strains have been shown to scavenge ROS and possess antioxidative ability, thus providing protection against oxidative stress and lipid peroxidation [12].…”
Section: Introductionmentioning
confidence: 99%